2000
DOI: 10.1046/j.1365-2354.2000.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in Iranian breast cancer patients before and after diagnosis

Abstract: A prospective study was conducted to measure anxiety and depression in Iranian breast cancer patients before and after diagnosis using the Hospital Anxiety and Depression Scale (HADS). The HADS was administered at two points in time: before diagnosis and 3 months after. In all, 168 breast cancer patients were interviewed. While 48% of patients had severe symptoms of anxiety at both baseline and follow-up, more than 60% of patients had no symptoms of depressive illness at pre-and post-diagnosis assessments. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
58
2
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 34 publications
11
58
2
7
Order By: Relevance
“…Global quality of life is a strong prognostic factor for survival in patients with lung cancer [23,30]. In our study, depression and anxiety were high in NSCLC cancer patients.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Global quality of life is a strong prognostic factor for survival in patients with lung cancer [23,30]. In our study, depression and anxiety were high in NSCLC cancer patients.…”
mentioning
confidence: 52%
“…Montazeri et al [23] reported that 10% of lung cancer patients had severe anxiety before diagnosis. Boncu et al [21] found that 12% of Turkish lung cancer patients were anxious.…”
mentioning
confidence: 99%
“…The BR-23 is a supplementary module of the EORTC QLQ C30, which covers the physical, personal, cognitive, emotional, and social domains. (Montazeri et al, 2000, Sprangers et al, 1996 The EORTC QLQ BR-23 incorporates two functional scales (Body Image and Sexual Functioning) and three symptom scales (Arm Symptoms, Breast Symptoms, and Systematic Therapy Side Effects). The remaining items assess sexual enjoyment and being upset by hair loss.…”
Section: Questionnairesmentioning
confidence: 99%
“…The remaining items assess sexual enjoyment and being upset by hair loss. The reliability and validity are adequate (Montazeri et al, 2000, Sprangers et al, 1996, Yun et al, 2004. In this study, only the scale Body Image was used.…”
Section: Questionnairesmentioning
confidence: 99%
“…Características da doença, como o mau prognóstico, a culpabilidade do doente relativamente a comportamentos de risco ao longo da vida, nomeadamente tabagismo 6 , e o estigma decorrente da associação entre o consumo de tabaco e o cancro do pulmão 7 são apontados como factores responsáveis por esta maior prevalência. 13 . Num outro estudo, envolvendo doentes com cancro do pulmão inoperável, sintomas de depressão foram referidos por 33 % dos doentes antes do tratamento, e persistiram em mais de 50% deles, sendo que os doentes com carcinoma de pequenas células apresentavam uma prevalên-cia 3 vezes superior 8 ; não serão alheias a este facto as diferenças de opções terapêuticas e de prognóstico nestes doentes, comparativamente aos doentes com carcinoma de não pequenas células.…”
Section: Vol XIV Nº 2 Março/abril 2008unclassified